Exploring the Possible Impact of Oral Nutritional Supplements on Children’s Oral Health: An In Vitro Investigation - Cynthia Anticona; Lena Hansson; Ingegerd Johansson; Pernilla Lif Holgerson (Dentistry Journal, 2024)
Eight pediatric oral nutritional supplements (ONSs) and 0.5% fat bovine milk were examined in vitro regarding their effect on the adhesion of three caries-related bacteria, Streptococcus mutans (strain CCUG 11877T), Lactobacillus gasseri (strain CCUG 31451), and Scardovia wiggsiae (strain CCUG 58090), to saliva-coated hydroxyapatite, as well as their pH and capacity to withstand pH changes. Bacteria were cultivated and radiolabeled. The adhesion assays used synthetic hydroxyapatite coated with whole or parotid saliva. Measurements of pH and titration of the products with HCl and NaOH were conducted in triplicate. Three ONSs promoted the S. mutans adhesion to saliva-coated hydroxyapatite (increase from 35% to >200%), supporting caries risk enhancement. S. wigssiae and L. gasseri adhered only to one and no ONS, respectively. Most supplements had limited buffering capacity to counteract acidification changes, suggesting their low capacity to neutralize acids, and one ONS showed a significant capacity to counteract basic changes, suggesting a high erosive potential. S. mutans adhesion was influenced by the ONS pH and volume NaOH added to reach pH 10. L. gasseri and S. wiggsiae adhesion was influenced by the ONSs’ carbohydrate and fat content. Interdisciplinary efforts are needed to increase awareness and prevent the possible negative impact of ONSs on children’s oral health.